MEMBANGUN CITY BRANDING SPARKLING SURABAYA MELALUI LAYANAN BUS SURABAYA SHOPPING AND CULINARY TRACK (SSCT) - Eva Hany Fanida; Indah Prabawati; Fitrotun Niswah; Trenda Aktiva Oktariyanda (Faculty of Social and Political Science, 2018)
City phenomena branding be trend in developed countries and developed with tourism sector.The potency advancement region, tourism city being one and phenomena draw to improve the attraction the community and created city branding surabaya including a town.In 2006, Surabaya city government with Surabaya tourism promotion board (STPB) launched Surabaya Sparkling as city brand surabaya city.Surabaya and city government STPB at that time launched branding many activities involving Surabaya city people. The design of esearch used was research and development (RnD). Research and development were developing or completing its turn as the improve existing products and could be accounted for. Of these products may be either standard operating procedures in the development of a model three-sectors partnership in building city shareholders have blocked a branding “Sparkling Surabaya” through services bus Surabaya Shopping and Culinary Track (SSCT). The result showed that it can be seen that there are still several weaknesses of service from the bus SSCT, this one of the development partnership tri-sector, comprising the government private and public.Third this element should form open collaboration and mutual provide added value when the collaboration partnership was taken to the technical csr creation will produce a comprehensive and working in all the circles.